2008
DOI: 10.1097/hjh.0b013e3282ff8864
|View full text |Cite
|
Sign up to set email alerts
|

The PHARAO study: prevention of hypertension with the angiotensin-converting enzyme inhibitor ramipril in patients with high-normal blood pressure – a prospective, randomized, controlled prevention trial of the German Hypertension League

Abstract: There is now good clinical evidence that patients with high-normal blood pressure (prehypertension) are more likely to progress to manifest hypertension than patients with optimal or normal blood pressure. Additional ambulatory blood pressure monitoring seems to be essential to achieve correct diagnosis. Treatment of patients with high-normal office blood pressure with the angiotensin-converting enzyme inhibitor was well tolerated, and significantly reduced the risk of progression to manifest hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 192 publications
(120 citation statements)
references
References 18 publications
4
108
0
5
Order By: Relevance
“…49,50) In addition to this, if the results of our current study are applicable to humans, lifelong ARB treatment starting at an early age in subjects with a genetic predisposition to hypertension would be expected to prevent blood pressure elevation and the development of cardiovascular organ injury throughout life.…”
Section: Discussionmentioning
confidence: 99%
“…49,50) In addition to this, if the results of our current study are applicable to humans, lifelong ARB treatment starting at an early age in subjects with a genetic predisposition to hypertension would be expected to prevent blood pressure elevation and the development of cardiovascular organ injury throughout life.…”
Section: Discussionmentioning
confidence: 99%
“…23 Hypertension was found to develop in 30.7% of the ramipril-treated patients compared with 42.9% of the controls, a relative risk reduction of 34.4%. These results suggested that treatment of prehypertensive patients with ACE inhibitor could prevent the development of hypertension in this population.…”
Section: Clinical Studies Of Hypertension Preventionmentioning
confidence: 99%
“…Both lifestyle changes (20) and drug therapy (21)(22)(23) have been shown at least temporarily to slow the progression of prehypertension into hypertension. The trials, up until now, have likely been too late to stop the progress, because, at least in the spontaneously hypertensive rat (24), antihypertensive therapy must be given much earlier in the lifespan to prevent the future development of hypertension.…”
Section: Value Of Therapymentioning
confidence: 99%